2022
DOI: 10.2147/opth.s373976
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of the Magnitude of Lens Rotation Following Implantation of a Toric Intraocular Lens with Modified Haptics

Abstract: Purpose To evaluate the reproducibility of magnitude of postoperative IOL rotation following implantation of a toric intraocular lens (IOL) with modified haptics, in comparison with a Proof-of-Concept (POC) study of prototype IOLs featuring the same haptic design. Patients and Methods A post-market, prospective, multicenter, single-arm, open-label clinical study was conducted. TECNIS Toric II IOL (Johnson & Johnson Vision, Irvine, CA, USA, Models ZCU150 to 600) were imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…Procedures for calculating IOL power and axis alignment are detailed in a prior publication. 10 Briefly, preoperative keratometry and biometry data including axial length, incision location, spherical equivalent IOL power, and the surgeon’s estimated surgically induced corneal astigmatism were used as inputs for the TECNIS Toric Calculator ( www.TecnisToricCalc.com ) or the surgeon’s preferred Toric Calculator. The investigators were instructed to use their standard IOL axis marking and small-incision, phacoemulsification, cataract extraction surgical technique.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Procedures for calculating IOL power and axis alignment are detailed in a prior publication. 10 Briefly, preoperative keratometry and biometry data including axial length, incision location, spherical equivalent IOL power, and the surgeon’s estimated surgically induced corneal astigmatism were used as inputs for the TECNIS Toric Calculator ( www.TecnisToricCalc.com ) or the surgeon’s preferred Toric Calculator. The investigators were instructed to use their standard IOL axis marking and small-incision, phacoemulsification, cataract extraction surgical technique.…”
Section: Methodsmentioning
confidence: 99%
“…Short-term rotational stability, defined as 1-day and 1-week postoperatively, and clinical performance of the Tecnis Toric II (Model ZCU) IOL from this were described in a previous publication. 10 In the current manuscript, short- and long-term lens rotation, visual acuity, manifest refraction, and patient and surgeon satisfaction were evaluated over a 3-month period following implantation.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 TECNIS Eyhance Toric II IOL has frosted haptics to increase surface friction between the capsular bag and the lens haptics, as well as a constant power pro le optic to improve intermediate vision. 10,[21][22][23] Takaku R et al reported that toric II IOL demonstrated higher rotational stability than toric I IOL with lower residual manifest astigmatism (p = 0.018), lower axis misalignment (p = 0.04), less incidence of misalignment > 10º (p = 0.0044), and a smaller degree of prediction errors (p = 0.043). 9 Osawa R. et al also reported the same results with rotational stability and an incidence of misalignment > 10º.…”
Section: Discussionmentioning
confidence: 99%
“… 24 The statistically significantly lower repositioning rate of the Tecnis Toric II vs the Tecnis Toric I IOLs in the present study corroborates this and other findings of a very low rate of rotation with the newer lens platform. 3 , 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“… 2 Maximum rotation of toric IOLs occurs in the early postoperative period, usually within the first few hours of cataract surgery, and very little rotation occurs after 1 week postoperatively. 2 , 3 Various modifiable and non-modifiable risk factors, including incomplete removal of ophthalmic viscosurgical devices; decentered, non-circular, or unusually large capsulorhexis; longer axial length/high myopia; larger capsular bag size; and fluctuations in intraocular pressure, have been found to be associated with an increased likelihood of toric IOL rotation. 4–7 IOL manufacturers have introduced a variety of innovations in IOL material and design to improve postoperative IOL stability and prevent IOL rotation even in the presence of risk factors.…”
Section: Introductionmentioning
confidence: 99%